Face Recognition For Home Security System Using Hybrid Fisher Linear Discriminant Algorithm - Zhi, Chua Min Zhi (2009)
This thesis proposes a dual-function face recognition home security system, using a hybrid FLD algorithm that compensates for probes that are not from the training gallery. The system is able to perform two major tasks of a home security system, which is face authentication and face identification. In face authentication, the system makes decisions whether a person can enter the premises or not. In face identification, the system identifies different individuals from the household.